2022
DOI: 10.1097/cmr.0000000000000850
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to anti-PD1 therapies in patients with advanced melanoma: systematic literature review and application of the Society for Immunotherapy of Cancer Immunotherapy Resistance Taskforce anti-PD1 resistance definitions

Abstract: Nearly half of advanced melanoma patients do not achieve a clinical response with anti-programmed cell death 1 protein (PD1) therapy (i.e. primary resistance) or initially achieve a clinical response but eventually progress during or following further treatment (i.e. secondary resistance). A consensus definition for tumor resistance to anti-PD1 monotherapy was published by Society for Immunotherapy of Cancer Immunotherapy Resistance Taskforce (SITC) in 2020. A systematic literature review (SLR) of clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
3
0
2
Order By: Relevance
“…The presence of the KIR3DS1 allele has correlated with decreased PFS in patients with NSCLC. Although not completely understood, assays have shown that this resistance may be due to natural killer (NK) cell dysfunction resulting in their inability to properly express PD-1 [ 48 ]. Further analysis involving randomized trials will be needed to confirm whether this genetic variant is a predictive marker for a patient's response to PD-1 inhibitor treatment.…”
Section: Reviewmentioning
confidence: 99%
“…The presence of the KIR3DS1 allele has correlated with decreased PFS in patients with NSCLC. Although not completely understood, assays have shown that this resistance may be due to natural killer (NK) cell dysfunction resulting in their inability to properly express PD-1 [ 48 ]. Further analysis involving randomized trials will be needed to confirm whether this genetic variant is a predictive marker for a patient's response to PD-1 inhibitor treatment.…”
Section: Reviewmentioning
confidence: 99%
“…In addition, PD-1-based immune checkpoint inhibitors are much less effective in uveal melanoma than in other types of melanoma (response rate for PD-1 antibody monotherapy 7%-12%; response rate for a combination of ipilimumab and nivolumab 10%-18%). 22,23 A positive treatment study in metastasized uveal melanoma was first published in 2021. 24 In this international, randomized study, the novel compound tebentafusp was compared with an established medication of the investigator's choice (pembrolizumab, ipilimumab, or dacarbazin).…”
Section: New Treatment Approach With Immtacs For Uveal Melanomamentioning
confidence: 99%
“…Due to the fact that BRAF mutations are not present in uveal melanomas, BRAF‐targeted therapies cannot be utilized for this condition. In addition, PD‐1‐based immune checkpoint inhibitors are much less effective in uveal melanoma than in other types of melanoma (response rate for PD‐1 antibody monotherapy 7%–12%; response rate for a combination of ipilimumab and nivolumab 10%–18%) 22,23 . A positive treatment study in metastasized uveal melanoma was first published in 2021 24 .…”
Section: New Treatment Approach With Immtacs For Uveal Melanomamentioning
confidence: 99%
“…Des Weiteren sind PD-1-basierte Immuncheckpoint-Inhibitionstherapien beim Uvea-Melanom weitaus weniger wirksam als bei anderen Melanomtypen (Ansprechrate einer PD-1-Monotherapie 7%-12%; Ansprechrate der Kombination aus Ipilimumab und Nivolumab 10%-18%). 22,23 Im Jahr 2021 wurde erstmals über eine positive Therapiestudie für das metastasierte Uvea-Melanom berichtet. 24 In dieser internationalen randomisierten Phase-III-Studie wurde das neue Medikament Tebentafusp im Vergleich zu investigators choice (Pembrolizumab, Ipilimumab, oder Dacarbazin) eingesetzt.…”
Section: Neuer Therapieansatz Mit Immtacs Beim Uvea-melanomunclassified
“…Aufgrund der fehlenden BRAF ‐Mutation kommen BRAF‐zielgerichtete Therapieansätze für das Uvea‐Melanom nicht in Betracht. Des Weiteren sind PD‐1‐basierte Immuncheckpoint‐Inhibitionstherapien beim Uvea‐Melanom weitaus weniger wirksam als bei anderen Melanomtypen (Ansprechrate einer PD‐1‐Monotherapie 7%–12%; Ansprechrate der Kombination aus Ipilimumab und Nivolumab 10%–18%) 22,23 . Im Jahr 2021 wurde erstmals über eine positive Therapiestudie für das metastasierte Uvea‐Melanom berichtet 24 .…”
Section: Neuer Therapieansatz Mit Immtacs Beim Uvea‐melanomunclassified